2020
DOI: 10.1016/j.cub.2020.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Sleepers Selectively Suppress Informative Inputs during Rapid Eye Movements

Abstract: Highlights d A neural decoder tracks speech processing in a cocktailparty paradigm during sleep d Speech is encoded in cortical activity during rapid eye movement (REM) sleep d Informative speech is selectively processed over meaningless speech during REM sleep d Informative speech is on the contrary selectively suppressed during eye movements within REM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
(57 reference statements)
1
19
0
Order By: Relevance
“…Studying REM-locked brain responses can be contrasted with studying brain activation associated with REM sleep episodes [ 27 , 28 ]. Our event-related fMRI findings showed that REM-locked brain activity is distinct from baseline brain activity during REM sleep [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studying REM-locked brain responses can be contrasted with studying brain activation associated with REM sleep episodes [ 27 , 28 ]. Our event-related fMRI findings showed that REM-locked brain activity is distinct from baseline brain activity during REM sleep [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, electrical responses from the brain during sleep have been investigated in many studies using the individual's own spoken name and other stimuli, but without any interactions that could be construed as two-way communication. [17][18][19][20][21][22][23] Whereas the idea of communicating interactively with sleeping individuals may seem outlandish, the legitimacy of this phenomenon is strongly supported by the following examples of successful two-way communication.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 1A). This phenomenon, however, is not limited to unicellular organisms, as recent studies have described a similar type of communication in cells from multicellular organisms, such as immune cells [2]. Indeed, during immune reactions, some cell types can associate in clusters that may be subjected to a similar quorum-type regulation.…”
mentioning
confidence: 98%
“…How does the brain balance these two opposing needs? In an elegantly designed experiment reported in a recent issue of Current Biology, Koroma and colleagues explored how the brain responds to speech during REM sleep [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation